1981
DOI: 10.1530/jrf.0.0620447
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and LH release in response to LH-RH and TRH in ewes during dioestrus, pregnancy and post partum

Abstract: Summary. With

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Seasonal or photoperiod-induced changes may re flect changes in secretion of several putative hypothalamic prolactin-releasing and inhibiting hormones including The role of TRH in mediating seasonal changes in pro lactin is unclear. Exogenous TRH elevates prolactin secre tion in sheep [4, 21,22], and both prolactin and thyroid-sti mulating hormone are elevated in sheep exposed to long photoperiods [12], These observations suggest that in creased TRH secretion could mediate both effects. However, active immunoneutralization of TRH in ewes does not prevent seasonal rhythms of prolactin secretion al though it reduces mean prolactin concentrations [5].…”
mentioning
confidence: 82%
“…Seasonal or photoperiod-induced changes may re flect changes in secretion of several putative hypothalamic prolactin-releasing and inhibiting hormones including The role of TRH in mediating seasonal changes in pro lactin is unclear. Exogenous TRH elevates prolactin secre tion in sheep [4, 21,22], and both prolactin and thyroid-sti mulating hormone are elevated in sheep exposed to long photoperiods [12], These observations suggest that in creased TRH secretion could mediate both effects. However, active immunoneutralization of TRH in ewes does not prevent seasonal rhythms of prolactin secretion al though it reduces mean prolactin concentrations [5].…”
mentioning
confidence: 82%
“…Plasma gonadotrophin concentrations (LH and FSH) decrease to a nadir in late gestation (Chamley et al, 1974a;Jenkin et al, 1977). Furthermore, the release of LH and FSH in response to the administration of gonadotrophin releasing hormone (GnRH) is suppressed to minimal values in late gestation (Chamley et al, 1974a,b;Jenkin and Heap, 1974;Jenkin et al, 1977), while the release of prolactin in response to thyrotrophin releasing hormone is increased (Wright et al, 1981). In contrast to the cycle, this suppression of gonadotrophin release is not associated with high plasma concentrations of inhibin, as Findlay et al (1991) demonstrated that immunoreactive inhibin concentrations decline from values equivalent to those observed during the cycle from day 40 of gestation to barely detectable concentrations by late gestation.…”
Section: Feedback Role Of Inhibin In Pregnant Ewesmentioning
confidence: 99%
“…Plasma folliclestimulating hormone (FSH) and prolactin were measured by previously published methods (Parrott & Davies 1977;Wright et al 1978Wright et al , 1981. The coefficients of variation within and between assays were < 14 and < 16%, respectively, for all hormones.…”
Section: Analyticalmentioning
confidence: 99%